2014
DOI: 10.3109/21681805.2014.920415
|View full text |Cite
|
Sign up to set email alerts
|

Do prostate cancer nomograms give accurate information when applied to European patients?

Abstract: To the authors' knowledge, this is the first head-to-head comparison of the accuracy of these commonly used risk calculators in a North European population. Caution should be used when counselling patients using nomograms. Although nomograms may be used as a guide, patients should be warned that they often have not been validated on different European populations and may give misleading information regarding a patient's specific risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
(49 reference statements)
3
11
0
1
Order By: Relevance
“…We also observed a clear unbalance towards sensitivity vs. specificity in the case of PT, and specificity vs. sensitivity in the case of MSKCCn and CAPRA, respectively. A possible explanation for our findings is that the results of clinical models depend on the population of application . This supports the idea that adding mpMRI can improve the models performance, given a more objective representation of cancer presence and extent.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We also observed a clear unbalance towards sensitivity vs. specificity in the case of PT, and specificity vs. sensitivity in the case of MSKCCn and CAPRA, respectively. A possible explanation for our findings is that the results of clinical models depend on the population of application . This supports the idea that adding mpMRI can improve the models performance, given a more objective representation of cancer presence and extent.…”
Section: Discussionsupporting
confidence: 81%
“…A possible explanation for our findings is that the results of clinical models depend on the population of application. 12,21 This supports the idea that adding mpMRI can improve the models performance, given a more objective representation of cancer presence and extent. Regardless of the radiologist experience, the combination of clinical models and mpMRI provided significantly robust tools in terms of discriminatory power, and increased the AUCs compared with clinical models alone.…”
Section: Discussionsupporting
confidence: 62%
“…The limitations of the present study include that it was performed in a single European centre. Previous reports demonstrated that the characteristics of patients treated at certain European institutions may not match those treated at other European or North American institutions . Second, based on the fact that patients in the present study exclusively underwent initial biopsies, very important differences in rates of upgrading might exist at repeat biopsy, which is integral to AS protocols and is often performed in time intervals of a year.…”
Section: Discussionmentioning
confidence: 82%
“…This notion suggests that extensive validation may be needed before one predictive tool is hastily adopted over others. Others have argued that the nomograms may not be generalizable to all patients (56, 57). A group of investigators used the information from 44 published prostate cancer prediction tools to devise a “cancer metagram” which incorporated 16 treatment options and 10 outcomes (cancer control, morbidity and survival).…”
Section: Current Predictive Toolsmentioning
confidence: 99%